KONTRIBUSI MINAT BACA DAN PENGUASAAN KALIMAT TERHADAP KETERAMPILAN MENULIS TEKS EKSPOSISI - Uli Wahyuni (Program Studi Pendidikan Bahasa dan Sastra Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2017)
The purpose of this research is to: (1) explaining there a contribution reading in the exposition text writing skills students class X SMA Negeri Kota Jambi; (2) explaining there a contribution mastery of sentence in the exposition text writing skills students class X SMA Negeri Kota Jambi; and (3) explaining there a contribution reading and mastery of sentence in the exposition tex twriting skills students class X SMA Negeri Kota Jambi. This research is a quantitative method used descriptive and correlational design. Samples were taken by proportional random sampling. Samples were taken 10% of the student population of each class, ie 80 people. Data of this research is the result of reading the score, score result mastery of sentence, and scores the results of the writing skills of exposition text converted into value. Based on the results of research and discussion that has been raised, it can be concluded that the interest in reading and mastery of sentence also determine students writing skills, especially writing skills exposition text. Exposition text writing skills students will increase if interest in reading and comprehension of sentences has also increased. So, interest in reading and mastery of mastery contribute significantly to the skill of writing texts exposition, although there are many other variables that affect writing skills.